Cash flow : operating performance of manufacturing industry in Malaysia - Ng, Hiu Chin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The objective of this paper is to examine the operating activities perfonnance across the manufacturing industries in Malaysia using financial accounting ratios. The variables chosen in the study include Return on Net Operating Assets ratio (RNOA), Operating Cash Flow ratio (OCF), Earning before Interest, Tax, Depreciation and Amortization Margin ratio (EBITDA Margin), Inventory Turnover ratio (IT) and Operating Cash Flow to Sales ratio (OCF/Sales). Each variable will be analyzed using Stata for 5 year-period from 2010-2014. The results of analysis found that the EBITDA Margin, IT and OCF/Sales did not translate into significant changes in RNOA. The lack of the significance in the ratios above implied that the study of profitability, efficiency and shor.t-tenn liquidity does not well explain the operating perfonnance of manufacturing industry i·n Malaysia. In contrast, changes in the OCF were significantly positive related with the changes in RNOA, indicating that the cash position of a company effects the operating perfonnance directly.